Creating a Rural Mandate: Impacting Institutional and State Policies - William H. Gray (Educational Considerations, 1986)
Critics of higher education point to the failure of land-grant universities and community colleges to serve their rural constituencies in meaningful ways. This paper examines one model for bridging the gap between rural problems and educational resources, emphasizing the need for a genuine partnership between rural people and educational professionals.